Utilization rate of fish resources in Banggai Laut waters - Aswad Eka Putra (Tomini Journal of Aquatic Science, 2020)
Capture fisheries is one of the leading sectors that drive the economy of Banggai Laut Regency. Improved fishing technology is related to fishing efforts that will affect the sustainability of fish resource stocks in the waters of Banggai Laut Regency. This study aims to identify the rate of utilization of fish resources in an effort to develop a sustainable fisheries sector in Banggai Laut waters. The method approach used is "Surplus Production". This method serves as an estimator of the relative abundance of a fish resource in the waters of Banggai Laut Regency which is based on the catch per unit of fishing effort. The results showed that the capability of the fishing fleet in Banggai Laut Regency has not been able to reach potential fishing areas. The catch per unit effort (CPUE) of fish resources in Banggai Laut Regency still shows an increasing trend with the highest rate of increase by other fish group including crustaceans and mollusks, about 0.160 tons/unit in the 2014-2016 period. Meanwhile, the catch per unit effort of the large pelagic fish group showed an increasing trend with the lowest rate of increase, about 0.001 tons/unit in the 2014-2016 period. Therefore the utilization rate of fish resources in the waters of Banggai Laut Regency is still classified as under exploited.